Numerical Study of Motion of a Cylinder Filled with Water on an Inclined Plane using Scilab: Marini Amalia Ocvianti, Yudhiakto Pramudya, Moh Irma Sukarelawan - Marini Amalia Ocvianti Marini Amalia Ocvianti; Yudhiakto Pramudya Yudhiakto Pramudya; Moh Irma Sukarelawan Moh Irma Sukarelawan (Jurnal Fisika dan Aplikasinya, 2021)
The velocity of the rolling motion is influenced by the shape of the object and its rotating axis. The cylinder motion on inclined plane has been investigated by number of research. However, the water filled cylinder need to be investigated further especially on the possibility moving sliding and rolling. Numerical study has been carried out on water filled cylinder modelling of frictionless sliding motion of point object, frictionless rolling motion, and rolling motion with friction on an inclined plane. By using the Euler method, data processing is carried out with the Scilab application. The resulting graph from running Scilab coding is a graph of v vs t and x vs t. We found the frictionless sliding motion produces the greatest velocity and distance because it is not influenced by friction and the object’s moment of inertia. Solid cylinder rolling with friction on an inclined plane produces the smallest velocity and distance due to the influence of friction and the moment of inertia of the object. These results indicate that a water filled cylinder can be considered a solid cylinder if ignoring all internal motion of water inside the cylinder.